DYNAMICS OF EMPLOYEE EXPENDITURE FROM THE PERSPECTIVE OF PERFORMANCE-BASED BUDGET EFFECTIVENESS AND EFFICIENCY ANALYSIS - Andi Yusuf Simatupang; Eka Nurmala Sari (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Employee Expenditure Dynamics and Performance-Based Budget Effectiveness: A Longitudinal Study at the Padangsidimpuan Police Resort. This study examines the asymmetric influence between Performance-Based Budgeting (PBB) implementation and employee expenditure dynamics on budget effectiveness and efficiency in police operational units characterized by extreme mandatory spending. Employing a mixed-data approach that integrates primary data from 24 respondents via questionnaires and longitudinal secondary data (2023–2025) consisting of SP2D realization, K PPN IPA scores, and AKIP evaluations, this research applies multiple linear regression to test causal relationships among variables. The primary scientific findings reveal three fundamental insights: (1) budget effectiveness emerges as a synergistic product of the normative PBB framework and adaptive expenditure dynamics mechanisms, rather than a single-variable outcome; (2) employee expenditure dynamics exert a dominant and significant influence on budget efficiency (coefficient = 1.086; p = 0.025), while PBB implementation remains insignificant in partial analysis; and (3) a paradox exists between technical performance improvement (IPA: 97.61 → 98.29) and managerial accountability stagnation (AKIP: BB category). These findings indicate that in mandatory-spending environments, administrative agility and close supervision become the primary determinants of efficiency, surpassing formal compliance with PBB principles. This study recommends implementing documented quarterly evaluations and optimizing close supervision as strategies to break AKIP stagnation, moving it from the BB to the A category.